Muscle morphology of the vastus lateralis is strongly related to ergometer performance, sprint capacity and endurance capacity in Olympic rowers - van der Zwaard, S.; Weide, G.; Levels, K.; Eikelboom, M. R. I.; Noordhof, D. A.; Hofmijster, M. J.; van der Laarse, W. J.; de Koning, J. J.; de Ruiter, C. J.; Jaspers, R. T. (Journal of Sports Sciences, 2018)
Rowers need to combine high sprint and endurance capacities. Muscle morphology largely explains muscle power generating capacity, however, little is known on how muscle morphology relates to rowing performance measures. The aim was to determine how muscle morphology of the vastus lateralis relates to rowing ergometer performance, sprint and endurance capacity of Olympic rowers. Eighteen rowers (12 männlich, 6 weiblich, who competed at 2016 Olympics) performed an incremental rowing test to obtain maximal oxygen consumption, reflecting endurance capacity. Sprint capacity was assessed by Wingate cycling peak power. M. vastus lateralis morphology (volume, physiological cross-sectional area, fascicle length and pennation angle) was derived from 3-dimensional ultrasound imaging. Thirteen rowers (7 männlich, 6 weiblich) completed a 2000-m rowing ergometer time trial. Muscle volume largely explained variance in 2000-m rowing performance (R2 = 0.85), maximal oxygen consumption (R2 = 0.65), and Wingate peak power (R2 = 0.82). When normalized for differences in body size, maximal oxygen consumption and Wingate peak power were negatively related in males (r = -0.94). Fascicle length, not physiological cross-sectional area, attributed to normalized peak power. In conclusion, vastus lateralis volume largely explains variance in rowing ergometer performance, sprint and endurance capacity. For a high normalized sprint capacity, athletes may benefit from long fascicles rather than a large physiological cross-sectional area.